2015
DOI: 10.1371/journal.pone.0123683
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Lapatinib in Therapy-Resistant HER2-Positive Circulating Tumor Cells in Metastatic Breast Cancer

Abstract: BackgroundTo evaluate the efficacy of lapatinib, a dual EGFR and HER2 tyrosine kinase inhibitor, in therapy-resistant HER2-positive CTCs in metastatic breast cancer (MBC).Patients and MethodsPatients with MBC and HER2-positive CTCs despite disease stabilization or response to prior therapy, received lapatinib 1500 mg daily in monthly cycles, till disease progression or CTC increase. CTC monitoring was performed by immunofluorescent microscopy using cytospins of peripheral blood mononuclear cells (PBMCs) double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…The potential to target CK+HER2+ CTCs with lapatinib or trastuzumab, has been recently reported [35, 36]. These observations suggest that therapies directed against specific targets could be necessary in order to eliminate CK+HER2+ chemotherapy-resistant CTCs.…”
Section: Discussionmentioning
confidence: 98%
“…The potential to target CK+HER2+ CTCs with lapatinib or trastuzumab, has been recently reported [35, 36]. These observations suggest that therapies directed against specific targets could be necessary in order to eliminate CK+HER2+ chemotherapy-resistant CTCs.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore the same group evaluated the efficacy of lapatinib, a dual EGFR and HER2 tyrosine kinase inhibitor, in therapyresistant HER2-positive CTCs in MBC in a phase 2 single-center study (NCT00694252). Lapatinib was effective in decreasing HER2-positive CTC counts in patients with MBC, irrespectively of the HER2 status of the primary tumor [169] . Two prospective trials are currently ongoing to demonstrate the clinical benefit of anti-HER2 therapy in patients with MBC considered as HER2-negative and HER2-positive CTCs.…”
Section: Targeting Ctcsmentioning
confidence: 90%
“…Interestingly, in the meta-analysis by Lee et al, patients with high sHER2 levels benefited from lapatinib therapy regardless of the HER2 status of the tumor (13). It has also been shown that HER2-targeted agents can eliminate HER2-positive CTCs in metastatic BC irrespectively of the HER2 status of the primary tumor (40). The question whether the choice of systemic treatment might be driven by blood-based biomarkers, is currently being clarified in the DETECT trials (2).…”
Section: Discussionmentioning
confidence: 99%